Identifying Infill Wall Failures in Kahramanmaraş Earthquakes and Strategies for Performance Improvement - Anıl Özdemir; Coşkun Çakmak (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Non-structural walls play a very important role in buildings, as they are used to create partitions and provide aesthetic appeal. However, their failures during earthquakes have been a recurring issue. Damage to the infill walls that occurred due to the Kahramanmaraş earthquake on February 6, 2023, was observed in residential and industrial buildings and especially in transformer structures that provide vital electricity distribution. This article presents the findings of field surveys conducted in Kahramanmaraş after recent earthquakes, focusing on non-structural wall collapses that obstructed mainly residential building entrances-exits and structures of particular importance. Within the scope of this study, deficiencies in the certification process in the field of infill walls were seen as the root of workmanship defects. Recommendations were made for the deficiencies in the certification process and for improving the process for the future. Infill walls shouldn’t exhibit out-of-plane behavior, causing loss of life and property and for escape routes to be blocked due to falling walls. With today's technology and engineering, it is possible to positively improve the energy consumption capacity and out-of-plane behavior of infill walls. In this context, a detailed literature review was conducted, and the different techniques used were explained in the article. In addition, explanations were given regarding the force of regulation in Türkiye. Within the scope of the study, the compatibility of regulations and national qualifications in the direction from the design to the production of infill walls is revealed.